Uniqueness in Inverse Electromagnetic Scattering by Locally Rough Surfaces with Phaseless Near-Field Data (Communications in Mathematical Research, 2025)
In this paper, we consider the reconstruction of a locally rough surface from phaseless near-field data generated by the incident electric dipoles.To obtain the uniqueness for this inverse problem, we use the superpositionof point sources as the incident waves. These point sources lie on an admissible surface. The measured data are collected from another admissible surfaceabove this locally rough surface. We derive the Rellich’s lemma and the reciprocity relation for the electric total fields. Based on them, we establish theuniqueness in phaseless inverse electromagnetic scattering by locally roughsurfaces.